Offer, conditions, and associativity: contributions on a survey of sports habits to municipal planning/Oferta, condiciones y asociatividad: aportes de una encuesta de hábitos deportivos a la planificación municipal - Carlos Matus Castillo; Diego Oliva González; Miguel Cornejo Améstica; Camilo Vargas Contreras (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The aim of the study was to describe the offer of sports and physical activity, the conditions for the practice of the population; and the characteristics of the sport association capacities, through a survey conducted among the inhabitants of a Chilean city, being the results a research contribution in the context of the elaboration of a Municipal Plan of Physical Activity and Sports. It is a descriptive, exploratory, and cross-sectional work, in which a standardized institutional in-person survey was applied. The sample was for convenience, but representative of the two sectors of the city surveyed, with a total of 209 people participating, men and women who were 15 years old and older. Descriptive statistics using frequency distribution was applied to analyze data. The results indicate that the perception about the level of physical activity practice and the number of sport facilities have increased, but they are still insufficient. A high use of municipal sports services has been also identified, with football being the most demanded sport offer. Regarding levels of participation in sport organizations, these have increased in relation to the national average; however, it still represents a low percentage. In addition, there is a tendency to practice sports preferably on an individual type.